Sharia financial literacy and digital message construction by Pegadaian: Content analysis of gold investment on Pegadaian's social media - Maulana Syarifudin; Angga Nur Rohman (The Journal of Religion and Communication Studies, 2026)
Background: This study stems from the increasing role of social media as the main space for Islamic financial education, especially that carried out by financial institutions such as Pegadaian. The research focuses on how Islamic financial literacy messages are constructed in Pegadaian's social media content on Instagram, TikTok, and YouTube. Methods: This study uses a qualitative approach with content analysis, with primary data in the form of Islamic financial literacy content documentation, including Instagram content "Is it permissible to buy gold in installments and online?"delivered by KH. Cholil Nafis, as well as YouTube content "What is sharia gold pawn?". The analysis was carried out by reading the signs, narratives, and visuals of the content through a semiotic approach, and linking them to the principles of sharia contracts in fiqh muamalah. Findings: The results of the study show that Pegadaian's Islamic financial literacy messages are constructed through simple educational narratives, the use of religious authority figures as symbolic legitimacy, and an emphasis on the clarity of the transaction process. Semiotically, the content conveys the meaning that Islamic gold investment and pawnbroking are safe, easy financial practices that are in line with Islamic values. Meanwhile, from a sharia contract perspective, the messages conveyed represent efforts to emphasize the clarity of the contract, the validity of the transaction object, and the avoidance of usury and gharar through sale and purchase contracts and rahn contracts. Conclusion: These findings confirm that Pegadaian's social media not only functions as a promotional medium but also as a space for the production of meaning and internalization of Islamic financial values in the context of digital communication. Novelty/Originality of this article: This study contributes to the study of Islamic finance communication by showing how digital messages can bridge normative Islamic principles with financial literacy practices in social media spaces.